Síntese e caracterização de Poli(L-co-DL ácido lático-co-policaprolactona)uretana. - Brandolise, Carolini Silva (2018)
Polyurethanes are applied for many purposes. This wide use is due to the versatility of these polymers, consisting of flexible and rigid segments, whose combination determines their characteristics. Therefore, the main objective of this work was to synthesize a biocompatible and biosorbable polyurethane, with an adequates properties to be used as a scaffold in meniscus regeneration. Prepolymer was obtained by bulk polymerization of L-lactide, D,L-lactide, polycaprolactone diol monomers. The initiator used was Tin II 2-ethylhexanoate. Materials was added to a flask under N2 atmosphere and immersed in an oil bath at 150 ºC, with stirring during 24 hours. Polyurethanes were obtained by solution polymerization of the prepolymer to a previous stage with 1,6-hexamethylene diisocyanate at a molar ratio of 1:8. Two polyurethanes were formed, using 2,1x10-4 mol of prepolymer and another one using 4,2x10-4 mol of prepolymer. The polyurethane synthesis was prepared on a flask under N2 atmosphere and immersed in oil at 70ºC with stirring during 6 hours. The average molecular weight of prepolymer was 104 g/mol obtained by GPC. Prepolymer and polyurethane were analyzed by FTIR and 1H NMR where results showed the presence of polycaprolactone, L and D,L-lactic acid and urethane groups in the polyurethane. Glass transition temperature, crystallization temperature and melt temperature were obtained by DSC analysis. The amount of prepolymer used in the polyurethane synthesis generated a difference on temperatures obtained by DSC analysis. The crystallinity of the polyurethanes were also verified by XRD. In the DMA analysis was observed that the polyurethane films melting around 60°C. It was observed also at DSC analysis. The DMA results corroborated with those of the XRD for the difference in crystallinity between the polyurethane films, the PU-C is more crystalline than the others. The TG and DTG analysis of polyurethanes demonstrated the presence of three stages of weight loss, with the Tonset changing with crystallinity value. The cell viability assay, based on the cytotoxicity of the polyurethanes, has shown that it is possible to proliferate cells in polyurethane synthetized. Therefore due to the characteristics presented by this polyurethane it could be applied as polymeric biomaterial in the field of tissue engineering.